Development of mucoadhesive floating hollow beads of acyclovir with gastroretentive properties. (August 2014) - Svirskis, Darren; Seyfoddin, Ali; Chalabi, Suna; In Kim, Joanne Hye; Langford, Christopher; Painter, Sivani; Al-Kassas, Raida
Abstract This study aimed at improving the oral bioavailability of acyclovir (ACV) through incorporating it into gastroretentive dosage form based on floating hollow chitosan beads. Hollow chitosan beads were prepared using a solvent free, ionotropic gelation method. The effect of formulation parameters, including chitosan molecular weight and drug concentration, on bead characteristics was studied. The drug containing formulations had yields >70.5 ± 0.31%. The entrapment efficiencies for the medium molecular weight chitosan formulations (56.29 ± 0.94%–62.75 ± 0.86%) was greater than the high molecular weight chitosan formulation (29.21 ± 0.89%). The density of all formulations was below that of gastric fluid, the greatest density observed was 0.60 ± 0.01 g cm−3. Unsurprisingly, the formulations were immediate bouyant to different degrees in both pH 1.2 and pH 6.8 media. In addition, the chitosan beads were all seen to swell in pH 1.2 media and demonstrated mucoadhesive properties. A sustained release profile was observed from the chitosan beads, the developed formulations released drug at slower rates than a marketed ACV oral tablet. The developed system has the dual advantages of being gastroretentive, to increase oral bioavailability and releasing drug in a controlled manner, to reduce the required frequency of administration thereby promoting patient adherence.